PTU-261 Alcohol misuse: refer and deter. Reducing re-admission rates for inpatient detoxification. (28th May 2012) - Beckett, V L; Ching, J; Wood, V; Singh, G
Abstract : Introduction: Alcohol abuse and related diseases are growing public health concerns. In the UK 26% of adults consume harmful quantities of alcohol. 1 Alcohol related admissions are increasing by 11% each year. 2 Yorkshire and Humber encompass one of the highest rates of alcohol misuse in the UK. NICE have developed a National Alcohol Strategy to target these issues which cost the UK economy £23 billion and NHS >£2.7 billion per year. 3 Despite initiatives to improve the quality of care and improve continuity between primary and secondary care, 58% of UK acute medical units lack an alcohol support service. Methods: We retrospectively audited the impact of the Alcohol specialist nurse (ASN) on readmission for inpatient detoxification between 2004 and 2011 at our hospital. This followed the establishment of an Alcohol Care Team in 2005 as recommended by The British Society of Gastroenterology. 2 Medical and surgical inpatients were included. Exclusion criteria: outpatient and A&E attendances, telephone consultations. Results: Between 2004 and 2011 the mean inpatient readmission rate for medical detoxification was 26.7% (484 readmissions, 1813 total admissions). On average 22.4% of medical and surgical inpatients were readmitted over the 7-year period (293 readmitted/1512 total admissions). Both the yearly readmission rate and percentage of patients requiring readmission increased by 589% and 689% respectively between 2004 and 2011, peaking in 2008–2009 predominantly due to an increase in patients readmitted once (four patients in 2004–2005 compared to 67 patients in 2008–2009). On average patients were readmitted 2.5 times for detoxification. The average period between readmissions was 9.4 months. 10% of patients were re-admitted for detoxification more than 5 times in this period (mode 6 readmissions, range 6–23 readmissions). Conclusion: Admission rates for inpatient detoxification are high. However, <25% of patients require readmission and only a minority require more than five detoxifications, thereby reflecting the efficacy of the ASN and Alcohol Care Team in minimising revolving door patients and the economic cost incurred. We recommend that all general hospitals should offer this service to effectively manage alcohol misuse. Competing interests: None declared. References: 1. BMA Board of Science . Alcohol Misuse . 2008. 2. Health Select Committee Report on Alcohol . 2010. 3. NHS Evidence . Alcohol Care Teams . 2011. 4. Moriarty K, et al. Alcohol Related Disease. 2010